Glycyrrhizin Ameliorate Ischemia Reperfusion Lung Injury through Downregulate TLR2 Signaling Cascade in Alveolar Macrophages - Fei, Lin; Jifeng, Feng; Tiantian, Wang; Yi, He; Linghui, Pan (Frontiers in Pharmacology, 2017)
This experiment was conducted to study whether pretreatment with Glycyrrhizin (GL) could ameliorate ischemia-reperfusion (I/R) lung injury and investigate the mechanisms of its protective effects in a mice model. Six-eight weeks male BALB/C mice were randomly assigned to four groups (n = 6): Control, Glycyrrhizin, I/R and I/R+Glycyrrhizin. Lung I/R was achieved by clamping the left hilus pulmonis. GL (200 mg/kg) was injected intraperitoneally 30 min before anesthesia. Measurement of pathohistological lung injury score, pulmonary permeability, isolated alveolar macrophages, inflammatory mediators, TLR2 and its downstream factors (MyD88, NF-κB) were performed. The results were as anticipated. Pathohistological evaluation indicated that GL significantly ameliorated I/R-induced lung injury, pulmonary permeability and edema. Pretreatment with GL significantly inhibited I/R-induced inflammation in lung tissues and BALF. In addition, GL significantly decreased I/R-induced isolated alveolar macrophages and suppressed I/R-induced expression of TLR2 and its downstream factors in lung tissues and alveolar macrophages. Collectively, our data indicated that pretreatment with GL could ameliorate I/R lung injury. The mechanisms of its protective effects might be inhibit I/R-induced inflammatory response through downregulate TLR2 signaling cascade in alveolar macrophages.